Teledermatology during COVID era: Our experience - Satish A Doddaballapur; Amrutha N Bangera; Radhika V Kaujalgi; Aparna A Dongare (Wolters Kluwer Medknow Publications, 2021)
Background: Telemedicine refers to "remote diagnosis and treatment of patients by means of telecommunication technology." Dermatology has a unique place in telemedicine as a reasonably accurate diagnosis can be established by history, clinical images, and real-time video consultation. Objectives: The aim was to assess the merits and demerits of teleconsultation in the period of lockdown due to COVID-19. Materials and Methods: An analysis of data of teleconsultation done in 84 patients between April 08, 2020 and May 19, 2020 was assessed. Results: The age group of patients ranged from 1 month to 95 years, with a preponderance of females over males. The most common skin condition in the study was eczema, followed by acne, psoriasis, and vitiligo. Among the total 84 patients, three patients were called for in-person consultation to eliminate the margin of error and six patients voluntarily reported for the follow-up to the clinic. Conclusion: Teledermatology during the COVID era safeguards both patients and health-care workers from exposure to the virus. Although faced with several challenges, teleconsultation when judiciously used can be a boon in the diagnosis of dermatological disorders, especially in susceptible individuals.